Selection of bacterial strains belonging to the astaxanthin producing Paracoccus genus - Thanh Xuan, Le Thi; Ha, Pham Thanh; Hoang, Nguyen Huy; Kim Lien, Nguyen Thi; Dieu Phuong, Nguyen Thi; Huy, Nguyen Quang; Thoa, Nguyen Kim (Vietnam Journal of Biotechnology, 2018)
Astaxanthin, a member of the carotenoid group, is an important additive not only in feed nutrition but also in providing the red color of salmon meat, cooked shellfish and koi fish. This leads to an increase in the commercial and aesthetic values for those aquatic products. In addition, astaxanthin is widely used in the food, pharmaceutical and cosmetic industries. Nowadays, astaxanthin has been mainly extracted from Haematococcus pluvialis and Phaffia rhodozyma. Moreover, some bacterial groups, especially Paracoccus genus including P. carotinifaciens, and P. haeundaensis have also been reported to synthesize a high level of astaxanthin. In this study, a number of bacterial strains belonging to Paracoccus genus isolated from several in-shore regions of Vietnam have been screened to find high astaxanthin producing strains for aquatic feed production. More than 90 colourful biosynthesis strains were isolated from 50 soil and water samples in different beaches and ramsa, of which 33 strains belong to negative bacterial group. Analysis of the extracted carotenoid mixtures obtained from the pellets of those strains by UV-Vis spectrophotometer and TLC reveals that 3 strains including C32, C38 and C47 are able to yield a high level of astaxanthin at 23 mg, 18 mg, and 11 mg astaxanthin per 1 g biomass, respectively. Based on the physiological, biochemical and 16S rRNA gene sequence, the C32 and C38 strains are most related to P. carotinifaciens whereas the C47 strain is most closely to P. kocurii.